6-HYDROXYISOCARYOPHYLLENE AND ISOCARYOPHYLLENIC ACID FROM BIRCH VEGETATIVE BUDS - Vedernikov, Dmitriy Nikolaevich; Teplyakova, Svetlana Vitalievna; Khoroshilova, Olesya Valerievna (Химия растительного сырья, 2018)
The new isocaryophyllene derivatives: 6-hydroxyisocaryophyllene [(1R,4Z,6R,9S)-8-methylene-11,11-dimethylbicyclo[7.2.0]undec-4-ene-6-ol], epoxide of 6-hydroxyisocaryophyllene [(6R)-hydroxy-(4R,5S)-epoxyisocaryophyllene [(1R,4R,5S,6R,9S)-4.5-epoxy-8-methylene-11,11-dimethylbicyclo[7.2.0]undeco-4-ene-6-ol], (6R)-acetoxyisocaryophyllene [(6R)-acetoxy-(1R,4Z,9S)-8-methylene-11,11-dimethylbicyclo[7.2.0]undec-4-ene], isocaryphyllenic acid [(1R,4E,9S)4-carboxy-8-methylene-11,11-dimethylbicyclo[7.2.0]undeco-4-ene] were first detected in the birch vegetative buds. 6-Hydroxyisocaryophyllene and epoxide of 6-hydroxyisocaryophyllene are isolated by from the Betula pendula Roth. birch buds etheric extract by chromatography on silica gel. (6R)-Acetoxyisocaryophyllene was synthesized. The structure of 6-hydroxyisocaryophyllene and epoxide of 6-hydroxyisocaryophyllene isolated from the buds were determined by NMR spectroscopy. Caryophyllenic acids are isolated from the ether extract with an aqueous solution of alkali. Caryophyllenic acids are separated by chromatography on silica gel. The structures of caryophyllenic acid and isocaryphyllenic acid isolated from the Betula grandifolia Litv., B. albo-sinensis Burk., B. fusca Pall.ex Georg, B. obscura A. Kotula, B. litwinowii Doluch., B. hallii Howell, B. grandifolia Litv. birch buds were determined by X-ray diffraction analysis. The physico-chemical characteristics and NMR data of 6-hydroxyisocaryophyllene, epoxide of 6-hydroxyisocaryophyllene and all the isolated acids are given. The obtained mixtures of compounds were analyzed by gas chromatography – mass spectrometry (GC-MS). The gas chromatographic retention indices of all identified compounds were determined.